RELAÇÕES HÍDRICAS E SOLUTOS ORGÂNICOS EM PLANTAS JOVENS DE Jatropha curcas L. SOB DIFERENTES REGIMES HÍDRICOS - Adenilda Ribeiro de Moura; Rejane Jurema Mansur Custódio Nogueira; José Antônio Aleixo da Silva; Tarcísio Viana de Lima (Ciência Florestal, 2016)
The objective of this study was to evaluate water and organic solutes in plants of Jatropha curcas L. exposed to water deficit and grown in a greenhouse. The design was completely randomized with four water treatments (-100% T1, T2 - 80%, T3 - T4 and 60% - 40% of pot capacity) and six replicates for 120 days. We evaluated the leaf water potential (Ψf), relative water content, content of chlorophyll a, b and total carotenoids and these pigments estimated by chlorophyll meter (SPAD). For biochemical evaluation were quantified levels of carbohydrates, proteins, amino acids and proline in the leaves at 60, 90 and 120 days, and at the end of the experiment, the same solutes in roots. There were significant differences between treatments for Ψf the three evaluation periods and between treatments. Plants with 60% and 40% CP showed more negative compared to control plants at noon. After 120 days treatment T4 decreased by 22 2% in relative water content compared to control. The carotenoids at 120 days ranged from 0.29 to 0.39 mg / g MF. Amino acids and carbohydrates in the leaves increased with 80% of treatment capacity pot to 120 days of differentiation water. At 60, 90 and 120 days, chlorophyll a showed an increase in Q4 compared to control. The content of chlorophyll by the SPAD index ranged from (26.1 to 34.5). The results suggest that Jatropha curcas is a drought tolerant species and with great economic potential for the Brazilian semiarid region.